IDENTIFIKASI BAHAYA DAN PENILAIAN RISIKO OPERATOR MESIN GERINDA - Rofika Anggun Thursina (The Indonesian Journal of Occupational Safety and Health, 2018)
Research in the fabrication unit of PT. Bangun Sarana Baja Gresik to determine hazard identification and risk assessment in grinding machine operators. This research uses Systematic Human Error Reduction and Prediction Approach (SHERPA) to determine error in identify hazard consisting of task stage, error mode, error description, consequence analysis and recovery analysis. The AS/NZS 4360: 2004 standard is used to determine the severity, likelihood and risk matrix scales in assessing risks consisting of frequency analysis, severity analysis, and criticality analysis that results in the level of risk at each stage of the task. Population in this research is all grinding machine operator at PT. BangunSarana Baja Gresik which are 60 operators. The sample of this research is as much as 20 grinding machine operatorsfabrication unit of PT. Bangun Sarana Baja Gresik with purposive sampling technique.Hazard identification on the grinding process such as falling material, unstable material condition, cracked grinding wheel, grinding wheel specifications are incompatible with the grinding machine and vice versa, the cable is flaked, melted, even broken, cracked cable terminal, starter (switch on/off) is damaged, sparks, gram sparks, ergonomic body positions, high speed grinding wheels, welding rays, noise and tool hand vibration can result in scratches, abrasions, dislocations, fractures, scratches broken grinding stones, electric shock, pincers, burns, low back pain, sore eyes, hand arm vibration syndrome and carpal tunnel syndrome in the worker's body. Risk assessment for low risk task stage is 6 error descriptions which means acceptable risk and no action required, medium risk is 31 error descriptions which means more alert and corrective action is recommended if cost effective, and high risk is 12 error descriptions which means the risk to be aware and there are actions needed to control the risks. Keywords: grinding, hazard identification, risk assessment